ANTESEDEN EMPLOYEE LOYALTY YANG DIMEDIASI OLEH WORK MOTIVATION KARYAWAN PERHOTELAN - ILMANSYAH, RIZKI; Berliyanti, Dita Oki; B. Medina Nilasari, (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
The hospitality industry in Indonesia has experienced significant growth, increasing the demand for service quality and employee loyalty. This study aims to analyze the effect of Remuneration System and Work Culture on Employee Loyalty, with Work Motivation as a mediating variable. This study uses a quantitative approach with a survey method of 201 employees of five-star hotels in DKI Jakarta. Data were analyzed using the PLS-SEM method. This study aims to analyze the effect of Remuneration System and Work Culture on Employee Loyalty, as well as the role of Work Motivation as a mediating variable in the context of the hospitality industry. The background of this study is based on the importance of maintaining employee loyalty in the service industry, especially five-star hotels, which are highly dependent on the quality of human resources. The results of the study indicate that Remuneration System and Work Culture have a positive and significant effect on Employee Loyalty, both directly and indirectly through the mediation of Work Motivation. Work motivation is proven to play an important role as a mediator, strengthening the relationship between the reward system and work culture with employee loyalty. These findings emphasize that strategies to increase employee loyalty must include fair and transparent remuneration policies, as well as the formation of a positive and supportive work culture.